A new tuberculate house gecko species (Squamata: Gekkonidae: Hemidactylus) from the northern Western Ghats of Maharashtra, India - Sayyed, Amit; Khot, Rahul; Purkayastha, Jayaditya (Zootaxa, 2025)
A new species of Hemidactylus is described from the high elevations of rocky landscapes at Chalkewadi Plateau in the northern Western Ghats of India. Based on phylogenetic analysis using the mitochondrial ND2 gene, the new species is a member of the H. murrayi clade within the H. brookii group. Morphological analysis also revealed diagnostic characters distinguishing it from its sister species, H. varadgirii. The species is medium-sized (SVL up to 54.3 mm), with 10–11 supralabials, 9–10 infralabials, canthal region with 18–21 scales on both sides, supraciliaries separated by 21–22 scales at mid-orbit, dorsal pholidosis heterogeneous, having 15–16 rows of tubercles across the midbody, 28–31 paravertebral tubercles between pelvic and pectoral limb insertions, midsagittal ventral scales 135–147, and 30–31 scales across the belly between the lowest rows of dorsal scales at midbody. Males have 7–9 femoral pores on each side, with six or seven poreless scales in between, and there are 7–8 lamellae beneath toe IV.